2020
DOI: 10.1021/acssensors.0c02335
|View full text |Cite
|
Sign up to set email alerts
|

A Bendable Biofuel Cell-Based Fully Integrated Biomedical Nanodevice for Point-of-Care Diagnosis of Scurvy

Abstract: Fully integrated nanodevices that allow the complete functional implementation without an external accessory or equipment are deemed to be one of the most ideal and ultimate goals for modern nanodevice design and construction. In this work, we demonstrate the first example of a bendable biofuel cell (BFC)-based fully integrated biomedical nanodevice with simple, palm-sized, easy-to-carry, pump-free, cost-saving, and easy-to-use features for the point-of-care (POC) diagnosis of scurvy from a single drop of untr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…Abiotic and enzymatic fuel cells have been successfully demonstrated as wearable and implantable power solutions. [90,[94][95][96] Because of potential safety issues of using microorganisms with infectious risks, MFCs had not been considered as a proper power source for any of BSN applications other than simulated studies. However, given that the human body is inhabited by millions of microorganisms, [97,98] the direct use of those human microorganisms as a fully self-sustaining biocatalyst in the MFC will significantly reduce foreign-body response and can be more attractive than toxic abiotic fuel cells and the unstable enzymatic fuel cells.…”
Section: Human Microbial Fuel Cells For Body Sensor Network (Bsns)mentioning
confidence: 99%
“…Abiotic and enzymatic fuel cells have been successfully demonstrated as wearable and implantable power solutions. [90,[94][95][96] Because of potential safety issues of using microorganisms with infectious risks, MFCs had not been considered as a proper power source for any of BSN applications other than simulated studies. However, given that the human body is inhabited by millions of microorganisms, [97,98] the direct use of those human microorganisms as a fully self-sustaining biocatalyst in the MFC will significantly reduce foreign-body response and can be more attractive than toxic abiotic fuel cells and the unstable enzymatic fuel cells.…”
Section: Human Microbial Fuel Cells For Body Sensor Network (Bsns)mentioning
confidence: 99%
“…This necessitates consideration of sensor performance within a broad context of power management, wireless communication, and data acquisition of fully integrated biochemical sensing systems. The recent emergence ,, of biofuel cell-based self-powered wearable sensors represents a successful pathway to realizing such a fully integrated platform.…”
Section: Future Opportunities and Commercializationmentioning
confidence: 99%
“…The intelligent non-invasive blood glucose monitoring system can avoid the discomfort caused by acupuncture, optimize the patient’s medical experience, and also bring great chances to medical diagnosis and health management. Besides sensor devices driven by biofuel cells used in sweat, Sun et al (2021b) reported a biofuel cell-driven medical nanodevice used in serum, which includes two parts: a vitamin C sensor chip (iezCard) for self-powered energy and an output chip for signal processing. The iezCard in the device integrates a special Kimwipes (A common laboratory paper) microfluidic channel, which can achieve efficient transmission of the serum to be tested.…”
Section: Intelligent Wearable Sensorsmentioning
confidence: 99%